MODIFIKASI MESIN PENYANGRAI BIJI-BIJIAN UNTUK MEMASAK KACANG GORENG PASIR KHAS JEPARA - -, Murharsito; Fauziah, Fitri Ella; Roosdhani, Mohamad Rifqy (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The regency of Jepara in Central Java Province has a special food called â€œoven peanutâ€, it is peanut which is roasted by using beach sand. One of the significant problems of the producer of this food is the production process which still be done in traditional method. This research attempts to overcome this problem by introduce the usage of machine to roast this food. The specification of this machine are made by the stainless steel, move in rotation with the motor of 0,25 PK equivalent with the electricity of 180 watt, and the heater is a LPG two burner stove, the temperature inside the machine can be controlled by the thermostat which has been installed to this machine. This research modifies the common grain roasted machine, in order to be fit to process the â€œoven peanutâ€, several modifications are applied. First to prevent the peanut breaks because of collision with the inner side of machine, the speed of machine rotation is decelerated; second to prevent the beach sand seep from the gap of material intake/exit valve, the front part of the machine is lifted up with lever. Several experiments in temperature setting then done to produce the best product, the result is the temperature of 60 Celsius degree produce the best product with the white color appearance and a good taste of peanut.Keywords: oven peanut, grain machine, modification